EVALUASI PELAKSANAAN KEBIJAKAN TENTANG PENERTIBAN DAN PEMBINAAN GELANDANGAN DAN PENGEMIS DI KOTA PEKANBARU ( STUDI PERATURAN DAERAH NOMOR 12 TAHUN 2008 ) - Junaidy, Robby Kurniawan; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Pekanbaru city make policy in the form of by law that is by law of number 12 year 2008 about Social Orderliness. But execution far from expected , to date problem of overcome difficult beggar and loiterer so that program K3 even also successful difficult in Pekanbaru. Evaluate policy represent activity to assess how far effectiveness of public policy utilize justified to constituent. There 6 criterion evaluate that is efektifitas, efficiency, sufficiency, generalization, responsivitas, and decision.In this research, researcher use informan of research through Key informan, where researcher have comprehended early about object of research and also research informan. Key of this Informan formal figure and the informal figure. Formal shop Head Sub Units of Social Social Rehabilitas On duty and Funeral of Town of Sexy Pekanbaru Head and Operational Set Of Police of Pamong of District public service of Town Pekanbaru, while informal figure of people who assumed to know about this problems, to obtain;get the information researcher use technique of Snowball Sampling.Pursuant to result interview known that By Law in Pekanbaru No 12 Year 2008 about Social Orderliness specially the Beggar and Loiterer Construction and Publisher have is not effective again, this matter seen from target and target which not yet maximal, inefficient because seen from expense facet, time, and the energy still less be, insufficient gratify requirement socialize, respon to this regulation a lot less know, hence from that this regulation have to be revised again to clarify and strengthen legal fundament in Beggar and Loiterer eradication execution which adapted for a condition or growth which walk.Keyword: Policy, implementation, Evaluation, By Law